Hubungan Dukungan Keluarga dengan Tingkat Kepatuhan Transfusi Darah pada Anak Penderita Talasemia Mayor di RSUD Umar Wirahadikusumah - Julia, Regina; Aisyah, Iis; Sejati, Amanda Puspanditaning (Yayasan Jompa Research and Development, 2026)
Thalassemia major is a condition requiring lifelong routine blood transfusion therapy, in which family support plays a vital role in treatment adherence to maintain the child's quality of life. This study aims to analyze the relationship between family support and blood transfusion compliance levels among children with thalassemia major at Umar Wirahadikusumah Regional General Hospital. A quantitative analytical design with a cross-sectional approach was employed. The sample consisted of 50 respondents, including parents or guardians of children aged 7–18 years, selected using a total sampling technique. Variables included family support as the independent variable and blood transfusion compliance level as the dependent variable, measured via questionnaires. Data were analyzed univariately and bivariately using the Spearman Rank correlation test with a significance level of α = 0,05. The results indicated that the majority of respondents had good family support (98%), with blood transfusion compliance categorized as high (48%) and moderate (52%). The Spearman test showed no significant relationship between family support and blood transfusion compliance levels (p = 0,380; r = 0,127). In conclusion, good family support does not automatically guarantee high blood transfusion compliance levels in school-age children and adolescents, which may be influenced by factors beyond the scope of this study.